2002
DOI: 10.1148/radiol.2221010481
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Aorta: Motion Artifact Reduction with Retrospective and Prospective Electrocardiography-assisted Multi–Detector Row CT

Abstract: The authors compared prospective (n = 20) and retrospective (n = 20) electrocardiography (ECG)-assisted multi-detector row computed tomography (CT) with non-ECG-assisted multi-detector row CT (n = 20) of the thoracic aorta with regard to reduction of motion-related artifacts. Image quality was rated for transverse source and sagittal oblique images of the thoracic aorta, including the aortic valve. ECG-assisted multi-detector row CT compared with non-ECG-assisted multi-detector row CT showed a significant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 14 publications
1
115
3
6
Order By: Relevance
“…aortic valve, aortic root, ascending aorta and coronary ostia), the application of either retrospective or prospective ECG-gating is considered mandatory in order to avoid artifacts caused by cardiac motion [2]. In case of non-diagnostic image quality, retrospectively ECG-gated acquisitions allow for alternate data reconstructions out of any other time point of the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…aortic valve, aortic root, ascending aorta and coronary ostia), the application of either retrospective or prospective ECG-gating is considered mandatory in order to avoid artifacts caused by cardiac motion [2]. In case of non-diagnostic image quality, retrospectively ECG-gated acquisitions allow for alternate data reconstructions out of any other time point of the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several papers have reported that the thoracic aorta motion artefact for computed tomography angiography of the whole aorta can be reduced by a high pitch mode (DHM) with 128-slice DSCT and an electrocardiogram-gated CT acquisition mode [17][18][19]. However, these special acquisition modes to reduce the motion artefacts are not necessarily available in all CT scanners.…”
Section: Discussionmentioning
confidence: 99%
“…зуализации сердца и коронарных артерий [27,28]. Эта же методика в последующем легла в основу качественной визуализации грудной аорты, позволив избежать пульсационных ар-тефактов [15,16,22,24,29,30]. Так, в начале 2000-х была предложена методика двухэтапно-го сканирования всей аорты с переменным питчем, когда грудной отдел сканируется с ЭКГ-синхронизацией, а брюшная часть -в обычном спиральном режиме.…”
Section: Fig 7 Msct Aorta Contrast Enhanced Scanunclassified